Poder, comunidades campesinas e industria minera: el gobierno comunal y el acceso a los recursos en el caso de Michiquillay* - Burneo, María Luisa; Chaparro Ortiz de Zevallos, Anahí (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
This paper analyzes changes in community governance in the contextof negotiations with a mining company. We focus on three issues:the role played by the community government on the regulation ofcommunity resources and territory, the diverse and complex intereststhat emerge in the presence of mining activity; and, the communityas a political institution confronting external pressures over its land.We develop a study case focusing on the negotiation process betweenthe Michiquillay peasant community and Anglo American MiningCompany in Cajamarca, Peru. This information was obtained doingfieldwork in the community in 2009. In our analysis we observe thatchanges on community resources regulation, its uses and valorization,as well as changes on the balance of power between economicand political actors, have created a greater level of complexity in thecommunity, creating new levels of community decision and spaces fordisputing resources’ control. At the same time, new inter communalconflicts emerge and fragmentation of community lands increases.In this context the community as an institution plays a central rolein the negotiation process over access productive resource and thedistribution of financial capital.

Este artículo analiza los cambios en el gobierno comunal en contextosde negociación minera. Nos centramos en tres temas: el roldel gobierno comunal en la regulación de los recursos comunalesy del territorio; la diversidad de intereses que surgen ante la presenciaminera, y la comunidad como institución política frente a lapresión externa sobre la tierra. Para ello, partimos de un estudiode caso: el proceso de negociación entre la comunidad campesinade Michiquillay y la empresa Anglo American, en Cajamarca, querealizamos a partir de un trabajo de campo en la comunidad. Delanálisis se desprende que las transformaciones en la regulación delos recursos comunales, sus usos y su valoración, así como el cambioen el peso de los actores económicos y políticos, han complejizadolas relaciones al interior de la comunidad y han creado nuevosniveles de toma de decisión y espacios de disputa por el controlde recursos. Al mismo tiempo que surgen nuevos conflictos intracomunalesy aumenta la fragmentación territorial, la comunidad como institución está jugando un rol central en la negociación yasumiendo nuevas funciones: ahora, el gobierno comunal no regulasolo el acceso a recursos productivos, sino también la distribucióndel capital financiero.
Power, peasant communities and mining industry: community government and access to resources in Michiquillay’s case
Keywords: Comunidades campesinas; Gobierno comunal; Tierras; Minería; Conflictos sociales; Consulta; Negociación; https://purl.org/pe-repo/ocde/ford#5.04.03